Dualism or Duality? - Buckham, John Wright (Harvard theological review, 1913)
Do we live in an intrinsically rent and warring world? or is the schism only apparent, veiling a fundamental and all-pervasive harmony? or is the universe of such a nature as to admit of a conflict which, though it has sprung up within it, is not of it?These three possibilities offer themselves to the mind that is trying to push through the world of appearances into the world of reality. The first is the conclusion of Dualism. The second is the conclusion of Monism. The third is an undifferentiated, but long prevalent and well-grounded, conviction, sometimes wrongly identified with dualism, sometimes with monism, but in reality independent of both. For want of a better term we may call it the principle of Duality.